SEXUAL HARASSMENT IN CAMP X-RAY MOVIE DIRECTED BY PETER SATTLER BASED ON FEMINISM PERSPECTIVE - Dwi Puji Hastuti; Rizky Mirani Desi Pratama; Endang Handayani (Universitas Negeri Gorontalo, 2022)
The analysis aims to find how sexual harassment appears, impacts sexual harassment, and feminism influenced the main character in Camp X-Ray movie. The method of this analysis is the descriptive qualitative method. The writer uses the sexual harassment theory by Kirillova and the feminism theory by Wicaksono dkk. The data about sexual harassment are taken from Camp X-Ray movie directed by Peter Sattler. The result of this analysis is sexual harassment appears, impacts of sexual harassment are frustrating. Feminism in this film focuses on fighting for women’s rights. As a result, Cole, as the main character, bravely fights the sexual harassment suffered by that sexual harassment does not occur again because with feminism, women have the freedom of speech, thought and protection for themselves in social life and other places